2015
DOI: 10.1021/acs.jpca.5b07749
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Nitric Oxide on Gas-Phase Cerium Oxide Clusters via Reactant Adsorption and Product Desorption Processes

Abstract: The reactivity of cerium oxide cluster cations, CenO2n+x(+) (n = 2-9, x = -1 to +2), with NO was investigated using gas-phase temperature-programmed desorption (TPD) combined with mass spectrometry. Target clusters were prepared in the gas phase via the laser ablation of a cerium oxide rod in the presence of oxygen, which was diluted using helium as a carrier gas. NO adsorbed onto stoichiometric and oxygen-rich clusters of CenO2n+x(+) (x = 0-2), forming CenO2n+x(NO)(+) (x = 0-2) species. Gas-phase TPD was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…21 In addition to this work, Aubriet et al have studied cerium oxyhydroxide cluster formation with mass spectrometry and density functional theory modeling. 22 Beyond water, the reactivity of cerium oxides with carbon and nitrogen oxides, [23][24][25][26][27][28] sulfur dioxide, 29 molecular oxygen, 30 and hydrocarbons 31,32 has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition to this work, Aubriet et al have studied cerium oxyhydroxide cluster formation with mass spectrometry and density functional theory modeling. 22 Beyond water, the reactivity of cerium oxides with carbon and nitrogen oxides, [23][24][25][26][27][28] sulfur dioxide, 29 molecular oxygen, 30 and hydrocarbons 31,32 has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…As for other transition-metal clusters, gas-phase reactions with NO were reported for Co n + , Ni n – , Cu n ±/0 , , Nb n ± , Rh n ± , , V n O m , Ta n O m , Cu n O m ± , , Ce n O m + , and Cu n Al + . Dissociative adsorption of NO on cobalt cluster cations, Co n + , , is followed by a release of N 2 to produce an O 2 adduct. , Sequential adsorption of NO and a release of N 2 have also been reported for Rh n ± . , NO molecules adsorbed on Cu n ±/0 do not exhibit a reaction between them, , whereas their reactivity is altered by oxidation or by doping of Al; oxidation of NO to NO 2 was reported for Cu n O m + , while a release of N 2 was observed for Cu n O 2 – and Cu n Al + . , It was also reported that NO is reduced to N 2 O by Cu nanoclusters on an Al 2 O 3 film .…”
Section: Introductionmentioning
confidence: 91%
“…For Ni n – and Nb n – , on the other hand, the production of NO 2 – and NO 3 – via an electron transfer from the cluster was observed as well as a release of N 2 , forming oxidized cluster anions. , For Nb n + , the formation of Nb n N 2 O + and Nb n NO 2 + was observed . As for oxide clusters of V, Ta, and Ce, NO adsorption is the only reaction channel for V n O m + and Ta n O m + , whereas NO is oxidized to NO 2 by Ce n O m + , forming Ce n O m –1 + . NO thus shows a rich variety of reactions depending on the catalysts.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations